Cultivating Olympic champions: A trampoline development environment from grass roots to podium. Issue 2 (4th May 2017) - Seanor, Michelle; Schinke, Robert J.; Stambulova, Natalia B.; Ross, Dave; Kpazai, Georges
ABSTRACT: Olympic athletes' training environments influence their abilities to develop and excel as Olympians. Our authors considered a Canadian trampoline training environment with a history of developing Olympic medal-winning athletes from the grassroots through to Olympic podium. The sport environment is presented, drawing upon guided walks, through a cursory description in accordance with the Environmental Success Factors model derived from a holistic ecological approach to talent development. This presentation of the Skyriders Training Environment (STE) reveals how environmental factors facilitate Olympic talent development culminating in the highest level of artistic sport performance.